The Alps as a Therapeutic Landscape in the Animation Series “Heidi, Girl of the Alps” (1974) - Oliver Salas Herrera (Revue de Géographie Alpine)
Due to the fiftieth anniversary of “Heidi, Girl of the Alps” (1974) –one of the most influential animated series of all time–, we propose an analysis of the therapeutic qualities of the Alps in this audiovisual adaptation and the relationship of its discourse with environmental concerns. For this analysis, we will consider the impact of Johanna Spyri’s original work on Japanese society, the artistic stamp of its director Isao Takahata, the production process and, especially, the importance of the narrative discourse and the setting of this adaptation. Focusing on this anime, we will study how the series, throughout its fifty-two episodes, uses various dramaturgical and visual resources to immerse viewers around the world in the imposing grandeur of the Alps, captivating us with its beauty and healing properties, while at the same time inviting us to reject the dehumanisation of the big cities. In conclusion, the audiovisual representation of Alpine nature in “Heidi, Girl from the Alps” (1974) is presented as a coprotagonist of this story, embodying a therapeutic environment that is connected to human nature. At the same time, the audiovisual narrative invites to a deeper understanding of the qualities of rural life and its relationship to sustainable resources.